PENYELESAIAN SENGKETA KEPEMILIKAN ASETYAYASAN DOMPET DHUAFA REPUBLIKA(Studi Kasus Putusan No. 282/Pdt.G/2013/PN.Bks.) - Ahmad Juwaini (2021)
PT. Syirkah Usaha Bersama bought land and buildings from PT. Putra Alvita Pratama that are located in West Java Province, Bekasi Regency, Bantar Gebang District, Cimuning Village, covering an area of 252 M2. Because the purchase is paid in installments, the buying and selling process is outlined in the Sale and Purchase Agreement. Furthermore, PT. Syirkah Usaha Bersama donated the land and building to the Dompet Dhuafa Republika Foundation. When the Dompet Dhuafa Republika Foundation was about to reverse the name of the land and building, it encountered difficulties. In dealing with this problem, Dompet Dhuafa Republika Foundation filed a civil suit at the Bekasi District Court with PT. Putra Alvita Pratama as Defendant I and PT. Syirkah Joint Venture as Defendant II. This research aims to determine the mechanism for dispute settlement of asset ownership and the efforts made after the dispute settlement mechanism has been adopted. This research is a normative and qualitative juridical study with a case study approach, for which data is analyzed by descriptive-prescriptive analysis. The results shows that the dispute resolution mechanism adopted was that the Bekasi District Court Judges decided with Verstek and granted the Plaintiff's claim. Furthermore, Dompet Dhuafa Republika Foundation makes a Sale and Purchase Deed and registers ownership of the land and building at the Bekasi National Land Agency office. Finally, the land certificate states that the land ownership belongs to the Dompet Dhuafa Republika Foundation.